An unusual case of adrenal insufficiency – schmidt's syndrome - JAGADEESAN MOHANAN; BANUPRIYA MOHAN; PRASANNA KARTHIK SUTHAKARAN; KANNAN RAJENDRAN; MAHENDRAKUMAR KALAPPAN; MAGESHKUMAR SIVANESAN (International Journal of Pharma and Bio Sciences, 2017)
Schmidt’s syndrome is a rare autoimmune endocrine disease in which the patient suffers from a combination of primary addison’s disease and autoimmune thyroid disorders. Schmidt’s syndrome is classified under inheritable Poly Glandular Autoimmune syndrome (PGA) as Type II. When immune dysfunction affects two or more endocrine glands and other non-endocrine immune disorders are present, the polyglandular autoimmune syndromes should be considered which are classified into two main types namely PGA type I and PGA type II. This syndrome is a very rare autoimmune disorder and difficult to diagnose because the symptoms of this syndrome depends on the endocrine gland that gets involved first. We report this case in which the patient had primary adrenal insufficiency, autoimmune hyperthyroidism and vitiligo and was diagnosed to have "Schmidt's syndrome" (PGA type II). Our patient was treated with corticosteroid supplementation and anti thyroid drugs following which she recovered.